Maternity behind bars: an exploration of physical and architectural conditions of the prison nursery of the CAI Vilma Curling Rivera in Costa Rica - Hernández Miranda, Andrea (2022)
This article provides an exploration, from an architectural lens, about the impact caused by the physical conditions of prison nurseries in children from ages zero to three who co-reside with their incarcerated mothers, specifically in the Módulo Materno Infantil (Maternal Child Module) of the CAI Vilma Curling Rivera. The current architectural conditions of this module are evaluated and the spatial characteristics that would strengthen infant-mother bonds, nurturing and early stimulation are researched, reducing the feelings of confinement, control and living behind bars. It is concluded that the massive scale of the penitentiary spaces, as well as the acoustic, climatic, sensorial, and lighting conditions, offer a depersonalized and hyper-stimulating experience. It identifies the need to break down the spaces into more intimate niches, with greater attention to textures, materialities, child scale and ergonomics of surfaces and furniture that allow to raise the degree of independence, self-esteem, and quality of life of its users.